TickNET—A Collaborative Public Health Approach to Tickborne Disease Surveillance and Research - Mead, Paul (Emerg Infect Dis, 2015)
TickNET, a public health network, was created in 2007 to foster greater collaboration between state health departments, academic centers, and the Centers for Disease Control and Prevention on surveillance and prevention of tickborne diseases. Research activities are conducted through the Emerging Infections Program and include laboratory surveys, high-quality prevention trials, and pathogen discovery.